2017
DOI: 10.1016/j.pharep.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TNF reduces mechanical orofacial hyperalgesia induced by Complete Freund’s Adjuvant by a TRPV1-dependent mechanism in mice

Abstract: We conclude that one of the possible regulatory mechanisms of TNF in pain involves upregulation of the nociceptor TRPV1, and that peripheral treatment with a selective anti-soluble TNF biologic can prevent hyperalgesia caused by inflammation in the orofacial region. Therefore, these new findings suggest that XPro1595 may serve as a novel treatment for orofacial pain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…These results suggested that these assessment methods, including the von Frey filament test, the bite force test, and eating pattern analysis, could be used to analyse different TMD mouse models. To verify the reliability of these methods, other types of TMD models are also needed, including mechanical stimulus-induced models, in which specific appliances have been employed to develop abnormal occlusal conditions, 39 , 40 the noxious stimulus model by orofacial formalin injection, 41 the TMJ inflammation mouse model, which is induced by the injection of complete Freund’s adjuvant, 42 , 43 and genetic mouse models. 13 , 44 Moreover, these methods should be further optimised in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that these assessment methods, including the von Frey filament test, the bite force test, and eating pattern analysis, could be used to analyse different TMD mouse models. To verify the reliability of these methods, other types of TMD models are also needed, including mechanical stimulus-induced models, in which specific appliances have been employed to develop abnormal occlusal conditions, 39 , 40 the noxious stimulus model by orofacial formalin injection, 41 the TMJ inflammation mouse model, which is induced by the injection of complete Freund’s adjuvant, 42 , 43 and genetic mouse models. 13 , 44 Moreover, these methods should be further optimised in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic data indicate that TNFR1 plays an essential role for pain development in males (Dellarole et al, 2014). Accordingly, it was shown that intraperitoneal administration of XPro1595 prevented complete Freund's adjuvant (CFA)induced mechanical hypersensitivity in male mice in a model of local CFA-induced model of orofacial pain (Lis et al, 2017). Similar, after CCI, systemic application of XPro1595 alleviated mechanical allodynia in males.…”
Section: Selective Neutralization Of Stnf By Dominant-negative Tnf Mumentioning
confidence: 99%
“…Current research suggests that inflammation is an influential participant factor in the pathophysiology of cerebral ischemia reperfusion injury. On one hand, inflammatory factors such as TNF-α and IL-1β activated by the microglia in the ischemic zone pose a toxic effect on ischemia brain neurons, thus exacerbate the damage of neurons (Lis et al, 2017). On the other hand, I/R can lead to the disrupt open of blood brain barrier (BBB), and peripheral infiltration of inflammatory cells into ischemic brain tissue, thus aggravate inflammatory lesions (Shichita et al, 2012).…”
Section: Western Blot Test Resultsmentioning
confidence: 99%